Study on flexible pavement failures in soft soil tropical regions - Muthuramalingam, Jayakumar; Soon, L. (2015)
© Published under licence by IOP Publishing Ltd.Road network system experienced rapid upgrowth since ages ago and it started developing in Malaysia during the colonization of British due to its significant impacts in transportation field. Flexible pavement, the major road network in Malaysia, has been deteriorating by various types of distresses which cause descending serviceability of the pavement structure. This paper discusses the pavement condition assessment carried out in Sarawak and Sabah, Malaysia to have design solutions for flexible pavement failures. Field tests were conducted to examine the subgrade strength of existing roads in Sarawak at various failure locations, to assess the impact of subgrade strength on pavement failures. Research outcomes from field condition assessment and subgrade testing showed that the critical causes of pavement failures are inadequate design and maintenance of drainage system and shoulder cross fall, along with inadequate pavement thickness provided by may be assuming the conservative value of soil strength at optimum moisture content, whereas the exiting and expected subgrade strengths at equilibrium moisture content are far below. Our further research shows that stabilized existing recycled asphalt and base materials to use as a sub-base along with bitumen stabilized open graded base in the pavement composition may be a viable solution for pavement failures.